2022
DOI: 10.1038/s41598-022-16193-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the simultaneous recognition of NEMO and acceptor ubiquitin by the HOIP NZF1 domain

Abstract: Ubiquitination of NEMO by the linear ubiquitin chain assembly complex (LUBAC) is essential for activating the canonical NF-κB signaling pathway. While the NZF1 domain of the HOIP subunit of LUBAC recognizes the NEMO substrate, it is unclear how it cooperates with the catalytic domains in the ubiquitination process. Here, we report a crystal structure of NEMO in complex with HOIP NZF1 and linear diubiquitin chains, in which the two proteins bind to distinct sites on NEMO. Moreover, the NZF1 domain simultaneousl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…This is in accordance with the 2:1 binding observed for the NEMO UBAN domain in complex with tetra-ubiquitin in solution (Vincendeau et al, 2016;Jussupow et al, 2020). Conversely, for Q330X NEMO, a 1:1 and K309) and an intact M1-ubiquitin-binding UBAN domain (residues 296-327) (Rahighi et al, 2022), but is neither modified by HOIP nor binds to M1-linked polyubiquitin. To find possible reasons for the differences between WT NEMO and Q330X NEMO, we used bioinformatic tools and biophysical approaches to characterize and compare the secondary and ternary structures of WT and mutant NEMO.…”
Section: Binding Of Q330x Nemo To M1-linked Tetra-ubiquitin Is Impairedsupporting
confidence: 86%
See 2 more Smart Citations
“…This is in accordance with the 2:1 binding observed for the NEMO UBAN domain in complex with tetra-ubiquitin in solution (Vincendeau et al, 2016;Jussupow et al, 2020). Conversely, for Q330X NEMO, a 1:1 and K309) and an intact M1-ubiquitin-binding UBAN domain (residues 296-327) (Rahighi et al, 2022), but is neither modified by HOIP nor binds to M1-linked polyubiquitin. To find possible reasons for the differences between WT NEMO and Q330X NEMO, we used bioinformatic tools and biophysical approaches to characterize and compare the secondary and ternary structures of WT and mutant NEMO.…”
Section: Binding Of Q330x Nemo To M1-linked Tetra-ubiquitin Is Impairedsupporting
confidence: 86%
“…In some conditions, NEMO is also covalently modified with M1-linked ubiquitin chains, although this has not been shown for endogenous NEMO upon IL-1β receptor activation ( Emmerich, 2013 ). NEMO interacts with HOIP upstream of the UBAN (ubiquitin binding in ABIN and NEMO) domain and with M1-linked ubiquitin via its UBAN domain, whereas binding to IKKα/β occurs through the N-terminal region of NEMO (residues 40–120) ( Tokunaga et al, 2009 ; Clark et al, 2013 ; Fujita et al, 2014 ; Rahighi et al, 2022 ). To test whether these interactions are impaired in Q330X NEMO, we performed co-immunoprecipitation experiments.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NEMO can also be modified with M1 chains promoting its oligomerisation and the trans-autophosphorylation of IKK⍺ and IKKβ (Tokunaga et al, 2009;Rahighi et al, 2022). Recently the roles of HOIP and M1 chains have been expanded to include proteostasis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that interaction between linear ubiquitin chains and NEMO (NF-κB essential modifier)/IKKɣ via its UBAN domain results in upregulation of NF-κB signalling (Rahighi et al ., 2009; Tobias L Haas et al ., 2009; Fujita et al ., 2014). NEMO can also be modified with M1 chains promoting its oligomerisation and the trans-autophosphorylation of IKK⍺ and IKKβ (Tokunaga et al ., 2009; Ikeda et al ., 2011; Rahighi et al ., 2022). Recently the roles of HOIP and M1 chains have been expanded to include proteostasis.…”
Section: Introductionmentioning
confidence: 99%